An Estimate of a Sectoral Model of Labor Mobility - Jovanovic, Boyan; Moffitt, Robert (Journal of Political Economy, 1990)
This paper develops a model of sectoral labor mobility and tests its main implications. The model nests two distinct hypotheses on the origin of mobility: (a) sectoral shocks and (b) worker-employer mismatch. We estimate the relative importance of each hypothesis and find that the bulk of labor mobility is caused by mismatch rather than by sectoral shift. We then try to put a value on society's match-specific information. That is, we ask to what extent the availability of the option to change jobs raises GNP. We find that the mobility option raises expected earnings by roughly between 8.5 percent and 13 percent of labor earnings, which translates to an increase in GNP of between 6 percent and 9 percent.